2012
DOI: 10.1089/scd.2011.0505
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-111 Stimulates Proliferation of Mouse Embryonic Stem Cells Through a Reduction of Gap Junctional Intercellular Communication via RhoA-Mediated Cx43 Phosphorylation and Dissociation of Cx43/ZO-1/Drebrin Complex

Abstract: Gap junctions within extracellular matrix (ECM)-defined boundaries ensure synchronous activity between cells destined to become functional mediators that regulate cell behavior. However, the role of ECM in connexin (Cx) function in mouse embryonic stem cells (mESCs) has not been elucidated. Therefore, we examined the role of laminin-111 in the control of Cx43 functions and related signal pathways in mESCs. ECM components (laminin-111, fibronectin, and collagen I) increased Cx43 phosphorylation and decreased Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have shown that the activation of Ga q or Gbc i results in the stimulation of phospholipase C activity, leading to phosphatidylinositol-(4,5)bisphosphate hydrolysis and Ca 21 mobilization from internal stores, and the subsequent activation of protein kinase C (PKC) [53,54]. In addition, LPA stimulates Ca 21 signaling and PKC activation, which are involved in proliferation, migration, or gap junction regulation in both embryonic stem cells and MSCs [55][56][57][58][59]. In this study, LPA stimulates PKC a, d, and f, which were abolished by Ga i and Ga q siRNA transfections as well as by Ptx pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the activation of Ga q or Gbc i results in the stimulation of phospholipase C activity, leading to phosphatidylinositol-(4,5)bisphosphate hydrolysis and Ca 21 mobilization from internal stores, and the subsequent activation of protein kinase C (PKC) [53,54]. In addition, LPA stimulates Ca 21 signaling and PKC activation, which are involved in proliferation, migration, or gap junction regulation in both embryonic stem cells and MSCs [55][56][57][58][59]. In this study, LPA stimulates PKC a, d, and f, which were abolished by Ga i and Ga q siRNA transfections as well as by Ptx pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, loss of Cx43 from neural crest cells results in a loss of β1-integrin immunoreactivity and a reduction in focal contacts (Xu et al, 2006). In contrast, gap junctional communication is reduced in embryonic stem cells (ESC) upon the activation of β1-integrins by laminin binding (Suh et al, 2012) while loss of β1-integrin from ESC derived cardiomyocytes results in the upregulation of connexin expression (Czyz, Guan, 2005). Here we find that loss of β1-integrin from the lens fibers results in an apparent redistribution of Cx50 from the broad faces of the fiber cell to all fiber cell membranes, perhaps explaining the increase in gap junctional coupling observed in cKO lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Stage-dependent expression of laminin in cartilage and cartilage-like tissue Increasing evidence indicates that chondrocytes are responsible for the production of various laminins ( Table 1a,b) that mainly locate in the PCM of cartilage SundarRaj et al, 1995). The expression of laminins varies during different developmental stages of cartilage and cartilage-like tissues ( Fig.…”
Section: Y Sun Et Almentioning
confidence: 97%
“…The interactions between laminins and chondrocytes can regulate many cell-biological functions, such as adhesion, migration and survival (Bulić, 1996;Francisco et al, 2014;SundarRaj et al, 1995). Laminin and cartilage regeneration chondrocytes and NP cells (Dürr et al, 1996;Gilchrist et al, 2011a;Gilchrist et al, 2011b).…”
Section: The Effect Of Laminin On Chondrocyte Functionmentioning
confidence: 99%